Socio-Political and Psychological Factors of Ulil Amri in Determining The Beginning of The Hijri Month - Abdul Azis (Jurnal Syntax Transformation, 2023)
The several approaches used in Indonesia to determine the start of the Islamic month are not the only factor; Ulil Amri, the person in charge, is also an aspect to consider. The study of this is necessary since Ulil Amri is typically thought of as the head of state or the administration. Ulil Amri's commands are deemed to have been disintegrated when something differs from a result of the government's judgment. This article attempts to examine the history of the notion of Ulil Amri as it emerged from various Muslim groups and organizations in Indonesia. Literature reviews were used to gather data about the concept of Ulil Amri as it was perceived by classical academics as well as as it was understood by various Muslim groups and organizations in Indonesia. This study demonstrates that the idea of Ulil Amri, which Muslims in Indonesia claim as their own, originates from ancient fiqh literature that makes reference to the ulama and the government (hukkam). These two ideas are also discussed in relation to the type of Ulil Amri that Muslims in Indonesia own. Other versions, such as Murshid Tariqah (Sufi Master) and the Jamaat chief, are the outgrowth of both thoughts, nevertheless. The social, religious, and political contexts of Indonesia contributed to the development of the Ulil Amri type variety. In addition, the similarity of the methods and criteria used by the Muslim community, with those used by the government, also influenced the difference in the concept of Ulil Amri.